Cannonball Chris - Marzollo, Jean.; Sims, Blanche (New York : Random House, 1987)
Chris tries to overcome his fear of jumping into deep water in time for the second grade swimming party.
Keywords: Fear -- Fiction; Swimming -- Fiction